IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY TERHADAP WARGA DAN LINGKUNGAN DI KELURAHAN GUNTUNG (STUDI KASUS PADA DEPARTEMEN HUMAS PT PUPUK KALTIM) - Ismail . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this article is to describe about the implementation of CSR program of PT. Pupuk Kaltim toward society and environment in Kelurahan Guntung, Bontang. The result shows that implementation of CSR program which is handled by public relation department of PT. Pupuk Kaltim bring high quality changes toward development accelerations in Kelurahan Guntung, in particular CSR environment and social development program.